Biotechnological Strategies for Effective Remediation of Polluted Soils - Koul, Bhupendra (Springer Singapore, 2018)
This book presents a comprehensive collection of various in situ and ex-situ soil remediation regimes that employ natural or genetically modified microbes, plants, and animals for the biodegradation of toxic compounds or hazardous waste into simpler non-toxic products. These techniques are demonstrated to be functionally effective in connection with physical, chemical, and biological strategies. Soil and water contamination through heavy metals, hydrocarbons and radioactive wastes is of global concern, as these factors have cumulative effects on the environment and human health through food-chain contamination. The book discusses the utilization of algae, plants, plant-associated bacteria, fungi (endophytic or rhizospheric) and certain lower animals for the sustainable bioremediation of organic and inorganic pollutants. In addition, it explores a number of more recent techniques like biochar and biofilms for carbon sequestration, soil conditioning and remediation, and water remediation. It highlights a number of recent advances in nanobioremediation, an emerging technology based on biosynthetic nanoparticles. Lastly, it presents illustrative case studies and highlights the successful treatment of polluted soils by means of these strategies. .